Normalcy, Race, and Biomedical Technology in Brazil: The Case of Low White Blood Cell Count - Calvo-González, Elena (Frontiers in Sociology, 2019)
This article explores the intersection between low-complexity biomedical technologies and ideas about race in Brazil. Using ethnographic material collected in the Northeastern city of Salvador, on the clinical management of low white blood cell count (leukopenia), and debates involving doctors, biomedical scientists and social movement activists on establishing racialised parameters in complete blood count tests, I explore how the notion of normalcy is connected to ideas about racial difference. Taken both at a population and individual bodily level, normalcy serves to contrast local history, portrayed as the result of widespread admixture between groups, with other national contexts, such as that of the United States. While a material body that cannot be classified as racially pure is seen as normal in the contemporary Brazilian context, nevertheless these pure racial types feature discursively as existing in a long lost past of Brazil’s history. At the same time, normalcy can also be locally challenged by certain actors, such as social movement activists, who underline the specific experience of certain racialised bodies, questioning the overarching national narratives of admixture and arguing for the need to recognise these bodies as normal as well, particularly in the context of political struggle for the reduction of social inequalities. These two ways in which normalcy appears articulated with local meanings of race gives way to seemingly contradictory and confronting discourses. Thus, racial categories that are explicitly not identified with admixture are seen as a thing of the past (the history of the Nation) and a thing of the future (a more racially equal country). This can be better comprehended by the process through which different historical discourses on racial difference in Brazil appear in connection with, or as a proxy for, ideas such as Nation, population or gender, originating from different places and moments in history.